Makna dalam Acara Ritual Adat Galih Tulang sebagai Bentuk Implementasi Hukum Lokal di Sumba Barat Daya - Prety Paskalina Pati Bani; Maria Virginia Jawaina Wotan; Stefanus Don Rade; Mahensa Tapatfeto; Elfege Kotoen Pandong; Lusia Melania Robin; Yohanes Lorensio Mbale; Risto Babtista Kehitos (Lembaga Pengembangan Kinerja Dosen, 2024)
The law of engagement is a concept that has existed since ancient times. In the past, engagements often relied on customary law and social norms applicable in a particular society. However, with the increasing development of society and trade, there is a need to have more formal legal rules to regulate agreements and agreements. The term